THE EFFECTIVENESS OF DETAILED READING STRATEGYIN IMPROVING STUDENTS' WRITING ACHIEVEMENT : AN EXPERIMENTAL STUDY AT SMAN 20 BANDUNG - Rida Winiarti, - (2009)
This research entitled "The Effectiveness of Detailed Reading Strategy in Improving Student's Writing Achievement" was aimed at finding out how and to what extent detailed reading strategy influence students' writing achievement. This research applied quasi-experimental design, which administered pretest and posttest. The samples involved were two groups served as experimental group and control group. The experimental group was given treatments in the period of one and a half month, while the control group was not given any treatment. In collecting the data, the instruments used were pretest, posttest, questionnaire, and document study. Thus, the t-test procedures were used in the data analysis. In addition, the data resulted from questionnaire that was administered to the experimental group and the data from studying the experimental group's pretest and posttest writings were analyzed. The result of the analysis provided the information of how and to what extent detailed reading strategy influenced students' writing achievement. The research findings showed that there were significant differences between the pretest and the posttest result of the two groups. The level of significance was 0.001 (=537;= 0.05). Briefly, detailed reading strategy is effective to improve students' writing achievement. In addition, the data resulted from questionnaire and document study showed that detailed reading strategy influenced writing achievement in five aspects (content, organization, vocabulary, grammar and mechanics) and the improvement of each aspect was varied. Content and organization aspects improved significantly while the other three aspects improved moderately. The writer recommends detailed reading strategy be applied in integrating reading and writing skill